Association of intentional cooling, achieved temperature and hypothermia duration with in-hospital mortality in patients treated with extracorporeal cardiopulmonary resuscitation: An analysis of the ELSO registry. (August 2022) - Nakashima, Takahiro; Ogata, Soshiro; Noguchi, Teruo; Nishimura, Kunihiro; Hsu, Cindy H; Sefa, Nana; Haas, Nathan L; Bĕlohlávek, Jan; Pellegrino, Vincent; Tonna, Joseph E; Haft, Jonathan; Neumar, Robert W
Abstract: Aim: To investigate whether intentional cooling, achieved temperature and hypothermia duration were associated with in-hospital death in patients treated with extracorporeal cardiopulmonary resuscitation (ECPR) for refractory cardiac arrest. Methods: This is a retrospective analysis of the Extracorporeal Life Support Organization Registry. Patients 18–79 years of age who received ECPR between 2010 and 2019 were included. We compared outcomes for intentional cooling versus no intentional cooling. Then, among those who completed intentional cooling, we compared the outcomes between i) achieved temperature ≤ 34 °C, 34–36 °C, and > 36 °C, and ii) duration ≤ 36 °C for < 12 h, 12–48 h, and ≥ 48 h. The primary outcome was in-hospital mortality within 90 days. Cox proportional hazard models were generated with adjustment for covariates. Results: Among 4, 214 ECPR patients, 1, 511 patients were included in the final analysis. After multivariable adjustment, there was no significant difference in in-hospital mortality between patients with intentional cooling and no intentional cooling (hazard ratio [HR], 1.06 [95% CI 0.93–1.21]; p  = 0.394). In the 609 patients who completed intentional cooling, temperature at 34–36 °C had a significantly lower adjusted HR for in-hospital mortality compared with > 36 °C (HR, 0.73 [0.55–0.96]; p  = 0.025). Moreover, temperature ≤ 36 °C for 12–48 h had a significantly lower adjusted HR for in-hospital mortality compared with ≤ 36 °C for < 12 h (HR, 0.69 [0.53–0.90]; p  = 0.005). Conclusion: Intentional cooling was not associated with lower in-hospital mortality in ECPR patients. However, among patients with intentional cooling, achieving temperature of 34–36 °C for 12–48 h was associated with lower in-hospital mortality.